The Sid Lapidus '59 Collection on Liberty and the American Revolution - Princeton University - Library (2021)
"The Sid Lapidus '59 Collection on Liberty and the American Revolution features books, pamphlets and prints representing the major themes of Lapidus's collecting: the intellectual origins of the American Revolution; the Revolution itself; the early years of the republic; the resulting spread of democratic ideas in the Atlantic world; and the effort to abolish the slave trade in both Great Britain and the United States. Presented here are scanned and text-searchable copies of an initial portion, more than 360 items. During 2021 and thereafter, more scanned books will be added, eventually covering the entire collection of more than 2200 items." [self-description]